Essays on production networks and international trade - Beltekian, Diana (2023)
Network analysis offers a rich framework to study questions of international trade. Trade has natural network applications with firms, sectors, and countries connected to buyers and suppliers through their sales within and across borders. Its applications have also been used to study financial, social, and transport networks within the economic discipline to deliver new insights. I apply network tools of analysis to address questions on the impact of network structure on future export competitiveness following a negative trade shock; and develop an endogenous production network model to quantify the bias of abstracting from the reorganisation of trade linkages that is assumed in a standard fixed production network model.